In vitro cytotoxic effects of Brazilian plant extracts on squamous cell carcinoma of the oral cavity - Joana Mattos Ozi; Ivana Barbosa Suffredini; Mateus Paciencia; Sergio Alexandre Frana; Luciano Lauria Dib (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Squamous cell carcinoma (SCC) is the most prevalent cancer of the oral cavity and the fifth most prevalent of all malignancies in males. Many researchers have attempted to develop new treatments that will improve the prognosis of SCC patients. Over 20% of the world's biodiversity is located within the Brazilian forests, but little is known about the chemical and/or pharmacological potential of these plants. Certain extracts obtained from Amazon and Atlantic Forest plants have previously been shown to have cytotoxic activity against various cancers. The aim of this study was to screen these extracts for cytotoxic activity against oral SCC cells. The extracts were analyzed for activity against the KB-ADL#12 cell line at various concentrations up to a maximum dose of 100 µg/mL. Comparisons with a control group were performed using one-way ANOVA. Significant cytotoxicity was induced by the extracts obtained from the aerial parts of Picrolemma sprucei (Simaroubaceae), from the leaves and stems of Laetia suaveolens (Salicaceae), from the aerial parts of Abarema auriculata (Fabaceae-Mimosoideae) and from the stem of A. auriculata.